RISK FACTORS AND SURVIVAL FOR PRIMARY THYROID LYMPHOMA: A CASE-CONTROL STUDY: Risk factors and survival for primary thyroid lymphoma - Slijepcevic, Nikola A.; Oluic, Branislav; Odalovic, Bozidar; Grujic, Milan; Zivaljevic, Vladan (Medicinska istraživanja, 2023)
Aim. The aim of the study was to evaluate demographic and clinical characteristics of patients with primary thyroid lymphoma (PTL), to identify risk factors associated with PTL and determine overall survival. Methods. We performed a retrospective case-control study of patients operated for PTL from 1995 to 2017. There were 41 patients with PTL that formed the cases group. The control group consisted of 82 patients with Hashimoto thyroiditis without concurrent thyroid disease. In statistical analysis we used standard descriptive statistics, logistic regression analysis, Kaplan-Meier survival curves and log rank test. Results. In the cases group there were 35 patients with non-Hodgkin lymphoma and six with Hodgkin lymphoma. The cases group and the control group had a predominantly female population (>90%). In the control group nearly 70% of patients were younger than 55 years, while in the cases group over 60% of patients were older than 55 years. Risk factors for the development of PTL in patients with Hashimoto thyroiditis are older age, long standing Hashimoto thyroiditis, an elevated level of TSH and a suspicious FNAB finding. Independent risk factors for PTL are an older age (>55 years) and long standing Hashimoto thyroiditis (>10 years). The mean overall survival for patients with PTL is 92.8 months. Patients with longstanding Hashimoto thyroiditis have a shorter survival (84 month). Conclusion. Patients older than 55 years with longstanding Hashimoto thyroiditis have a higher risk of developing PTL. Additionally, patients with longstanding Hashimoto thyroiditis have worse prognosis compared to other patients with PTL.